India's Recent Macroeconomic Performance : An Assessment and Way Forward - Kapur, Muneesh (IMF Working Papers; Working Paper, 2014)
The macroeconomic policy response in India after the North Atlantic financial crisis (NAFC) was rapid. The overshooting of the stimulus and its gradual withdrawal sowed seeds for inflationary and BoP pressures and growth slowdown, then exacerbated by domestic policy bottlenecks and volatility in international financial markets during mid-2013. Appropriate domestic oil prices and fiscal consolidation will contribute to the recovery of private sector investment. Fiscal consolidation would also facilitate a reduction in inflation, which would moderate gold imports and favorably impact real exchange rate and current account deficit.